Genological-pragmatic plots in selected works by Marek Cybulski - Pałucka-Czerniak, Iwona (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The article contains an overview of the basic historiosophical principles and methodological choices that Professor Marek Cybulski, a historian of Polish language, is guided by in his research. At the basis of contemporary historical-linguistic reflection lies the experience of philological analysis. First of all, in the centre of the study, specific language forms are used for a specific purpose, the meaning of which is described by the analysis of the communication function and the pragmatic situation. In historical-linguistic research, it is expedient to apply philological methods, enriched with socio-linguistic and pragmatic descriptions, taking into account their modifications resulting from various factors, including: phenomenon and text values, universality and representativeness. The assessment of the degree of universality or scale of the phenomenon can be based on both intuitional and self-experienced reflections, as well as on specific data acquired in turnout studies. The analysis is primarily concerned with universal, repetitive, stable phenomena, constituting a permanent and important element of human communication. The basic research sources should be varied, and among them a considerable value is attributed to manuscript, usable, authentic texts.